The Polls—Trends: British Public Opinion towards EU Membership. Issue 4 (28th December 2021) - Hobolt, Sara B; Tilley, James
Abstract: In 2020, the United Kingdom became the first member state to leave the European Union (EU). This followed a referendum on membership in 2016. Public opinion about EU membership has been regularly measured since the 1970s in Britain. In this Poll Trends article, we document the changes in sentiment towards the EU in a variety of different ways. We report on attitudes towards the cost and benefits; national and European identities; support for continued membership of the EU; specific policy preferences towards Britain's involvement with the EU; vote intention in a referendum on membership pre- and post- the 2016 referendum; and the prevalence of new political identities created by the referendum.